2018
DOI: 10.1007/s00540-018-2505-9
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of effect of dexmedetomidine and lidocaine on intracranial and systemic hemodynamic response to chest physiotherapy and tracheal suctioning in patients with severe traumatic brain injury

Abstract: Both dexmedetomidine and lidocaine were effective to blunt rise in HR, MAP and ICP in response to CP and TS in patients with sTBI. However, intravenous dexmedetomidine caused significant decrease in MAP and CPP as compared to the baseline and lidocaine.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 25 publications
0
24
0
1
Order By: Relevance
“…The variations in the stimulation of the airway caused by the differences in suction methods, suction duration, negative pressure applied, and suction tube insertion depth, are re ected in ICP changes [4-11, 16, 17]. It has been previously demonstrated that ES is an important factor affecting ICP [12][13][14][15][16]. The results of the current work showed that the average peak value of ICP in the experimental group was 15.57 ± 12.31 mmHg, while that in the control group was 18.24 ± 8.99 mmHg.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The variations in the stimulation of the airway caused by the differences in suction methods, suction duration, negative pressure applied, and suction tube insertion depth, are re ected in ICP changes [4-11, 16, 17]. It has been previously demonstrated that ES is an important factor affecting ICP [12][13][14][15][16]. The results of the current work showed that the average peak value of ICP in the experimental group was 15.57 ± 12.31 mmHg, while that in the control group was 18.24 ± 8.99 mmHg.…”
Section: Discussionmentioning
confidence: 99%
“…ES stimulates airway mucosa, triggers cough re ex, induces bronchospasm, decreases blood oxygen saturation, and increases intracranial pressure. Severe airway stimulation may lead to adverse consequences [1], such as severe cough, increased chest pressure, a sudden rise in blood pressure, increased cerebral perfusion, increased intracranial pressure (ICP) caused by cerebral vasospasm, and increased risk of vascular rupture [12][13][14][15][16]. The stimulation of the airway caused by different suction modes and duration, the amount of negative pressure applied, and the depth of suction tube insertion lead to re exive ICP changes [4-11, 16, 17].…”
Section: Introductionmentioning
confidence: 99%
“…The variations in the stimulation of the airway caused by the differences in suction methods, suction duration, negative pressure applied, and suction tube insertion depth, are re ected in ICP changes [4][5][6][9][10][11][12]. Previous studies had demonstrated that ES was an important factor affecting ICP [6][7][8]. The results of the current work showed that the average peak value of ICP in the experimental group was 15.57 ± 12.31 mmHg, while that in the control group was 18.24 ± 8.99 mmHg.…”
Section: Propofol Sedation Before Es Helps To Stabilize Intracranial mentioning
confidence: 99%
“…The sputum suction tube repeatedly stimulates the respiratory mucosa, resulting in varying degrees of choking and coughing in patients. In severe cases, it causes a decrease in blood oxygen saturation and an increase in ICP, producing discomfort [4][5][6][7][8]. Propofol is a short-term anesthesia drug, which is rapidly distributed in the entire organism within 40 seconds after intravenous injection.…”
Section: Propofol Sedation Ensures Es Effectmentioning
confidence: 99%
See 1 more Smart Citation